(untitled) (KYAMC Journal, 2017)
This cross sectional study was carried out in SSMC for a period of one year from July 2007 to June 2008 to evaluate rK39 based ELISA and KAtex tests for diagnosis of Kala-azar. Total 150 patients were selected clinically. For this study rK39 ICT was regarded as confirmatory test according to national guideline. Among 150, total 100 cases were confirmed to be positive for Kala-azar by rK39 ICT test. Age and sex matched 25 healthy persons each from endemic and non-endemic area were taken as control. Among the 100 sero confirmed cases KAtex was positive in 87 (sensitivity of 87%) while ELISA was positive in 98 cases (sensitivity 98%). Among the 50 controls none were positive by KAtex test while 1 (one) ELISA test was positive resulting in specificity of these tests 100% and 98% respectively. The result of the study clearly showed superiority of rK39 antigen based ELISA in respect of sensitivity and KAtex in respect of specificity. KYAMC Journal Vol. 6, No.-1, Jul 2015, Page 574-578